2020
DOI: 10.1007/s00428-020-02954-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocyte abundance and programmed death-ligand 1 expression in metaplastic breast carcinoma: implications for distinct immune microenvironments in different metaplastic components

Abstract: Both stromal tumor-infiltrating lymphocytes (sTILs) and programmed death-ligand 1 (PD-L1) affect responses to immunotherapy; however, the extent of sTIL and PD-L1 expression within various metaplastic components in metaplastic breast carcinoma (MBC), which are critical for the characterization of immune microenvironments, remains unreported. We profiled sTIL infiltration and PD-L1 expression in different metaplastic components of specimens from 82 MBC patients. The overall positivity for high or intermediate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…Chao et al [ 134 ] found sqCC MBC exhibiting most TILs of all the MBC subtypes. Similarly, Lien et al [ 138 ] reported that sqCC exhibited the highest positivity rate of TILs, while matrix-producing carcinoma had the lowest. Kalaw et al [ 135 ] did not observe significant association between TILs and morphological subtypes of MBCs but observed that PD-L1 positive TILs were enriched in squamous cell carcinomas.…”
Section: Immune Response and Immune Therapy In Mbcmentioning
confidence: 89%
See 3 more Smart Citations
“…Chao et al [ 134 ] found sqCC MBC exhibiting most TILs of all the MBC subtypes. Similarly, Lien et al [ 138 ] reported that sqCC exhibited the highest positivity rate of TILs, while matrix-producing carcinoma had the lowest. Kalaw et al [ 135 ] did not observe significant association between TILs and morphological subtypes of MBCs but observed that PD-L1 positive TILs were enriched in squamous cell carcinomas.…”
Section: Immune Response and Immune Therapy In Mbcmentioning
confidence: 89%
“…In contrast, no significant difference in the expression of PD-L1 in stromal cells was found among different types of tumors [ 133 , 135 , 137 ] (see Table 1 ). Additionally, no differences in PD-L1 expression in tumor cells were observed among different subtypes of MBC [ 135 , 138 ]. Lien et al [ 138 ] reported an increase of PD-L1 expression in immune cells of MBC with squamous differentiation.…”
Section: Immune Response and Immune Therapy In Mbcmentioning
confidence: 99%
See 2 more Smart Citations
“…staining in ≥1% tumor cells; ≥5% staining in peri-tumoral regions 38% tumor cell; 48% tumor immune microenvironment Morgan et al 62 2020 146 TNBC (27 MpBC) SP263 Memb. staining in ≥1% of tumor cells; immune cells MpBC 30% tum, 73% immune; TNBC 10% tum, 59% immune Afkhani et al 49 2019 14 MpBC SP263 >1+ intensity in >1% immune cells 50% immune cells Lien et al 63 2020 82 MpBC SP142 % tumor cells; immune cells as % of tumor area 17% tum; 48% immune cell Kalaw et al 64 2020 125 MpBC E1L3N ≥5% tumor/immune cells displaying cyto. or memb.…”
Section: Precision Oncology For Mpbcmentioning
confidence: 99%